Aqueous binder for negative electrode material of lithium ion battery and preparation method thereof
By using a water-based adhesive mixed with the first acrylate and the second acrylate polymer in the lithium-ion battery, the problem of performance optimization of the negative electrode material of the lithium-ion battery in the prior art is solved, and high dispersion, adhesion and The synergistic effect of cohesive strength extends the battery cycle life.
Patent Information
- Application Number
- CN202311193463.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-15
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2043-09-15
AI Technical Summary
The existing water-based adhesive cannot obtain comprehensive performance optimization of lithium-ion battery negative electrode materials through mixing, resulting in fragile hardness of the electrode sheet, powder loss, cracking and other problems, and the advantages of low internal resistance and long circulation cannot be fully utilized.
Van der Waal, who combines carboxyl polar groups by adsorbing and wrapping on the surface of active particles through unevenly distributed hydrophilic and hydrophobic chain segments. Force action improves particle dispersion and stability and reduces internal resistance.
The synergistic effect of high dispersion, adhesion and cohesion strength is achieved, which extends the battery cycle life and improves the stability and battery performance of the pole plate.
Smart Images

Figure BDA0004451436110000011 
Figure BDA0004451436110000051 
Figure BDA0004451436110000091
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of water-based adhesives, and in particular, to a water-based adhesive for lithium-ion battery negative electrode materials and a preparation method thereof. Background Art
[0002] Aqueous binders are raw materials used to disperse the positive and / or negative electrode materials in lithium-ion batteries into slurry and bond them to the pole pieces. Aqueous binders have an important influence on the dispersibility of positive and / or negative electrode materials, the adhesion of coatings to pole pieces, and other properties, and therefore can directly affect the performance of the battery cell, such as cycle life, resistance, etc.
[0003] Commonly used polymer materials for water-based adhesives include polyacrylate PAA, styrene-butadiene latex SBR, sodium carboxymethyl cellulose CMC, etc. Different polymer materials have different advantages and disadvantages. Mixing different polymer materials to integrate the advantages of different polymer materials and make up for the shortcomings is a common method, but there are still some limitations. For example, although the CMC+PAA mixture has higher adhesion and cohesion, the final battery has low internal resistance and better cycle, but the pole piece is hard and brittle, and it is easy to lose powder and crack during the pole piece manufacturing process, affecting the final battery performance. Although the PAA+SBR mixture can improve the manufacturing process, it cannot give full play to the advantages of PAA's low internal resistance and long cycle. The pole piece obtained by CMC+SBR or some other mixing methods has insufficient peeling force and is prone to powder loss during the subsequent coating process. Summary of the invention
[0004] In order to solve the technical problem in the prior art that water-based adhesives cannot obtain better comprehensive performance by mixing, the present application provides a water-based adhesive for lithium-ion battery negative electrode materials and a preparation method thereof.
[0005] This application adopts the following technical solutions:
[0006] An aqueous binder for a negative electrode material of a lithium ion battery, comprising a first acrylate polymer and a second acrylate polymer;
[0007] The preparation method of the first acrylate polymer is as follows: a first monomer combination consisting of a first hydrophilic monomer and a first hydrophobic monomer is polymerized in water for a first time, and then a second monomer combination consisting of a second hydrophilic monomer and a second hydrophobic monomer is added to perform a second polymerization, thereby obtaining the first acrylate polymer;
[0008] The general formula of the second acrylate polymer is as shown in the following formula (1):
[0009]
[0010] Among them, R1 , R 2 and R 3 independently selected from H or C1-C4 alkyl, R 4 Selected from H, Na + , Li + and K + At least one of R 5 is selected from C1-C36 alkyl, C2-C36 substituted alkyl, amino or substituted amino, R 6 The general formula is -R 7 CN, R 7 is absent or is at least one selected from C1-C4 alkylene, a>0, b≥0, c>0, a:b:c=2-5:0-4:2-5.
[0011] Preferably, the concentration of the aqueous binder is 3-60wt%.
[0012] Preferably, the weight proportion of the first hydrophilic monomer in the first monomer combination is 60-100%.
[0013] Preferably, the weight proportion of the second hydrophilic monomer in the second monomer combination is 0-60%.
[0014] Preferably, the weight ratio of the first monomer combination to the second monomer combination is 1:9-9:1.
[0015] Preferably, the first hydrophilic monomer and the second hydrophilic monomer are independently selected from the general formula CH2=CR 8 R 9 The monomers, R 8 is selected from H or C1-C4 alkyl, R 9 Selected from -CONH2, -CONHCH3, -CONHCH2CH3, -CON(CH3)2, -CON(CH2CH3)2, -CONHCH2OH, -CONHCH2CH2OH, -COOCH2CH2OH, -COOCH2CH2CH2OH, -COOCH2CHCH3OH, -COOCH2CH2CH2CH2OH, -COO(CH2CH2O) a H and -COO(CH2) b PO3H, and / or one or more of the organic structures containing -COOM, -(C6H5)COOM, -SO3M and -(C6H5)SO3M functional groups, a=1-18, b=1-12, M is selected from H, Li + 、Na + and K + One or more of the .
[0016] Preferably, the first hydrophobic monomer and the second hydrophobic monomer are independently selected from the group consisting of: 10 R 11 The monomers, R 10 is selected from H or C1-C4 alkyl, R 11 Selected from -COOC n H 2n+1 and -C m H 2m One or more of CN, n=1-18, m=0-6.
[0017] Preferably, the conversion rate of the first monomer combination after the first polymerization is not less than 70%.
[0018] Preferably, the weight ratio of the first acrylate polymer to the second acrylate polymer is 1:9-9:1.
[0019] The method for preparing the aqueous binder for lithium-ion battery negative electrode materials described in any of the above embodiments comprises mixing a first aqueous solution containing the first acrylate polymer and a second aqueous solution containing the second acrylate polymer.
[0020] The principle of the water-based adhesive of the present application is as follows: two acrylic polymers with different structures are mixed in the present application. The first acrylic polymer has an uneven distribution of hydrophilic and hydrophobic parts on its polymer chain, and the hydrophobic chain segment is more inclined to adsorb on the surface of the active particles, thereby playing a role in wrapping and dispersing the active particles. However, the active particles are not necessarily stably suspended in the slurry, and there must be sufficient steric hindrance to ensure that the particles do not re-agglomerate; the second acrylic polymer, the polar groups such as carboxyl groups on its chain segments can extend in the aqueous phase with the hydrophilic groups of the first component adsorbed on the surface of the active particles. The water segments more effectively interact with each other through van der Waals forces, thereby ensuring sufficient steric hindrance between the particles, and the active particles in the slurry have high particle dispersibility and dispersion stability at the same time; in addition, due to the improvement in slurry stability, compared with the first aqueous solution of the first acrylate polymer used alone as an aqueous adhesive, the proportion of the first acrylate polymer adsorbed on the surface of the active particles in the aqueous adhesive slurry of the present application can be lower, thereby reducing the effect of excessive polymer coating on the active particles on the lithium ion conduction at the interface between the active particles and the electrolyte, and the final battery cell has a lower internal resistance. Therefore, the technical effect of the aqueous adhesive of the present application is not just a simple superposition of the performance of the first aqueous solution and the second aqueous solution, but also realizes the synergy of the efficacy of the two acrylate polymers, and has better overall performance.
[0021] In summary, this application has the following beneficial effects:
[0022] 1. The aqueous adhesive of the present application combines the characteristics of the first acrylate polymer and the second acrylate polymer, and has a higher adhesion to the copper foil and a higher electrode cohesive strength while achieving high dispersibility of the negative electrode active material particles. Higher cohesive strength can provide better electrode stability, thereby improving the stability of the electrode structure during battery cycling and extending battery life.
[0023] 2. This application designs the structure of the acrylate polymer through monomer selection and preparation process research, and realizes the synergistic effect of the two acrylate polymers: the first acrylate polymer has good dispersibility on the negative electrode active material particles, and the prepared slurry has good dispersibility and dispersion stability; the second acrylate polymer has higher adhesion to the copper foil and higher electrode cohesive strength. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described in detail below.
[0025] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.
[0026] The aqueous binder for lithium-ion battery negative electrode materials of the present application comprises a first acrylate polymer and a second acrylate polymer; the weight ratio of the first acrylate polymer to the second acrylate polymer can be 1:9-9:1, for example, 1:9, 1:8, 1:7, 1:6, 1:5, 1:4, 1:3, 1:2, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, etc. Further, the weight ratio can be 1:7-7:1.
[0027] In the present application, the concentration of the aqueous adhesive is 3-60wt%. For example, it can be 3wt%, 5wt%, 8wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt% and the like.
[0028] The first acrylate polymer of the present application can be directly presented in the form of a first aqueous solution, for example, obtained by a free radical polymerization reaction in an aqueous medium; the second acrylate polymer can be directly presented in the form of a second aqueous solution, for example, obtained by a free radical polymerization reaction in an aqueous medium.
[0029] On the other hand, the present application proposes a method for preparing the above-mentioned aqueous binder for lithium-ion battery negative electrode materials, which is mixed with a first aqueous solution containing a first acrylate polymer and a second aqueous solution containing a second acrylate polymer. For example, it can be composed of a first aqueous solution with a first acrylate polymer content of 30wt% and a second aqueous solution with a second acrylate polymer content of 40wt% in a weight ratio of 2:1, or a first aqueous solution with a first acrylate polymer content of 40wt% and a second aqueous solution with a second acrylate polymer content of 20wt% in a weight ratio of 3:1, or a first aqueous solution with a first acrylate polymer content of 30wt% and a second aqueous solution with a second acrylate polymer content of 50wt% in a weight ratio of 1:2, or a first aqueous solution with a first acrylate polymer content of 20wt% and a second aqueous solution with a second acrylate polymer content of 40wt% in a weight ratio of 1:1, or a first aqueous solution with a first acrylate polymer content of 40wt% and a second aqueous solution with a second acrylate polymer content of 40wt% in a weight ratio of 1:1, etc.
[0030] First Acrylate Polymer
[0031] The preparation method of the first acrylate polymer is as follows: a first monomer combination consisting of a first hydrophilic monomer and a first hydrophobic monomer is polymerized in water for a first time, and then a second monomer combination consisting of a second hydrophilic monomer and a second hydrophobic monomer is added to perform a second polymerization to obtain the first acrylate polymer;
[0032] The weight proportion of the first hydrophilic monomer in the first monomer combination is 60-100%. Further, the weight proportion of the first hydrophilic monomer in the first monomer combination is 65-90%, for example, the weight proportion can be 65%, 70%, 75%, 80%, 85%, 90%, 95%, etc.
[0033] The weight proportion of the second hydrophilic monomer in the second monomer combination is 0-60%. Further, the weight proportion of the second hydrophilic monomer in the second monomer combination is 10-55%, for example, the weight proportion can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, etc.
[0034] Wherein, the weight ratio of the first monomer combination to the second monomer combination is 1:9-9:1. For example, the weight ratio of the first monomer combination to the second monomer combination can be 1:9, 1:8, 1:7, 1:6, 1:5, 1:4, 1:3, 1:2, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, etc. Further, the weight ratio can be 1:7-7:1.
[0035] Wherein the first hydrophilic monomer and the second hydrophilic monomer are independently selected from the general formula CH2=CR 8 R 9 The monomers, R 8 is selected from H or C1-C4 alkyl, R 9 Selected from -CONH2, -CONHCH3, -CONHCH2CH3, -CON(CH3)2, -CON(CH2CH3)2, -CONHCH2OH, -CONHCH2CH2OH, -COOCH2CH2OH, -COOCH2CH2CH2OH, -COOCH2CHCH3OH, -COOCH2CH2CH2CH2OH, -COO(CH2CH2O) a H and -COO(CH2) b PO3H, and / or one or more of the organic structures containing -COOM, -(C6H5)COOM, -SO3M and -(C6H5)SO3M functional groups, a=1-18, b=1-12, M is selected from H, Li + 、Na + and K + For example, the first hydrophilic monomer and the second hydrophilic monomer can be hydroxyethyl acrylate, acrylic acid, sodium acrylate, hydroxypropyl acrylate, methacrylic acid, sodium methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, polyethylene glycol acrylate, etc.
[0036] Wherein the first hydrophobic monomer and the second hydrophobic monomer are independently selected from the chemical formula CH2=CR 10 R 11 The monomers, R 10 is selected from H or C1-C4 alkyl, R 11 Selected from -COOC n H 2n+1 and -C m H 2m CN, n = 1-18, m = 0-6. For example, the first hydrophobic monomer and the second hydrophobic monomer can be acrylonitrile, methacrylonitrile, 3-butenenitrile, ethyl acrylate, butyl acrylate, butyl methacrylate, isooctyl acrylate, lauryl acrylate, stearic acid ester, lauryl methacrylate, etc.
[0037] Wherein, the conversion rate of the first monomer combination after the first polymerization is not less than 70%. The conversion rate of the first monomer combination after the first polymerization is not less than 70%, which has little effect on the weight ratio of the second hydrophilic monomer and the second hydrophobic monomer in the added second monomer combination. Further, the conversion rate of the first monomer combination after the first polymerization is not less than 75%, or not less than 80%.
[0038] Second Acrylate Polymer
[0039] The general formula of the second acrylate polymer is shown in the following formula (1):
[0040]
[0041] Among them, R 1 , R 2 and R 3 independently selected from H or C1-C4 alkyl, R 4 Selected from H, Na + , Li + and K + At least one of R 5 R is selected from C1-C36 alkyl, C2-C36 substituted alkyl, amino or substituted amino, and the substituted amino may be N,N-dimethylamino, N,N-diethylamino, N-methylamino, N-ethylamino, N-hydroxymethylamino, N-hydroxyethylamino, etc.; 6 The general formula is -R 7 CN, R 7 is absent or is at least one selected from C1-C4 alkylene, a>0, b≥0, c>0, a:b:c=2-5:0-4:2-5.
[0042] There are three monomers used in the second acrylic ester polymer, namely CH2=CR corresponding to a 1 COOR 4 、b corresponding to CH2=CR 2 COOR 5 、c corresponding to CH2=CR 3 COOR 6 For example, CH2=CR 1 COOR 4 The monomer can be acrylic acid, sodium acrylate, methacrylic acid, sodium methacrylate, etc. CH2=CR 2 COOR 5 In monomer, R 5 Selected from C2-C18 alkyl, C2-C18 substituted alkyl, amino or substituted amino, for example, CH2=CR 2 COOR 5The monomer may be an acrylate monomer, or an acrylamide monomer, or a combination of an acrylate monomer and an acrylamide monomer in a weight ratio of 1:1-10:1. For example, the acrylate monomer may be butyl acrylate, octyl acrylate, isooctyl acrylate, lauryl acrylate, stearic acrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxybutyl acrylate, etc. The acrylate monomer may also include methyl methacrylate, ethyl methacrylate, etc. The acrylamide monomer may be acrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, N-methylacrylamide, N-ethylacrylamide, N,N-dihydroxymethylacrylamide, N-hydroxymethylacrylamide, N,N-hydroxyethylacrylamide, etc. For example, CH2=CR 3 COOR 6 The monomer may be acrylonitrile, methacrylonitrile, 3-butenenitrile or the like.
[0043] The second acrylate polymer can be prepared as follows: add a certain amount of water in a container, heat it to the polymerization reaction temperature, drop a mixture of three monomers, or drop the three monomers separately, and simultaneously drop a free radical initiator aqueous solution (such as ammonium persulfate aqueous solution), drop the dropwise addition within 10 minutes to 4 hours, and continue to react for 0 to 8 hours after the dropwise addition. The preparation method can also be: add a certain amount of water in a container, add a mixture of three monomers, heat it to the polymerization reaction temperature, drop a free radical initiator aqueous solution (such as ammonium persulfate aqueous solution), drop the dropwise addition within 10 minutes to 4 hours, and continue to react for 0 to 8 hours after the dropwise addition.
[0044] The technical solution of the present application is described in detail below in combination with the preparation examples, embodiments and comparative examples. Unless otherwise specified, the parts in the following preparation examples, embodiments and comparative examples are parts by weight.
[0045] Preparation Example 1-4 Preparation of the First Acrylate Polymer
[0046] Preparation Example 1
[0047] 400 parts of water are added to a reaction container, and a first monomer combination consisting of 45 parts of methacrylic acid, 15 parts of acrylamide, 10 parts of hydroxypropyl acrylate and 30 parts of acrylonitrile, and 5 parts of sodium bicarbonate are added under stirring at 180 rpm, and the mixture is evenly mixed. The temperature is increased to 75° C., and 10 parts of an aqueous solution containing 0.2 parts of ammonium persulfate are added dropwise within 30 minutes. After the addition is completed, the mixture is kept warm for 90 minutes, and the conversion rate of the first monomer combination is measured to be 74%. A second monomer combination consisting of 10 parts of methacrylic acid and 40 parts of acrylonitrile and 20 parts of water are added, and the stirring is increased to 250 rpm, and the mixture is fully mixed. The temperature is increased to 73° C., and 10 parts of an aqueous solution containing 0.3 parts of ammonium persulfate are added dropwise within 30 minutes. The mixture is kept warm for 180 minutes. After the insulation is completed, sodium bicarbonate and water are added, and the pH is adjusted to 7.0-7.5, and the solid content is 16 wt %, to obtain a first aqueous solution.
[0048] Preparation Example 2
[0049] The difference between Preparation Example 2 and Preparation Example 1 is that in Preparation Example 1, the second monomer combination is composed of 20 parts of methacrylic acid and 80 parts of acrylonitrile, and 10 parts of an aqueous solution containing 0.3 parts of ammonium persulfate is adjusted to 10 parts of an aqueous solution containing 0.6 parts of ammonium persulfate. The remaining steps remain unchanged.
[0050] Preparation Example 3
[0051] 400 parts of water are added to a reaction container, and a first monomer combination consisting of 20 parts of methacrylic acid, 10 parts of acrylamide, 10 parts of hydroxyethyl acrylate and 10 parts of acrylonitrile, and 3 parts of sodium bicarbonate are added under stirring at 180 rpm, and the mixture is evenly mixed. The temperature is raised to 75° C., and 5 parts of an aqueous solution containing 0.2 parts of ammonium persulfate are added dropwise within 30 minutes. After the addition is completed, the mixture is kept warm for reaction for 120 minutes, and the monomer conversion rate is measured to be 82%. A second monomer combination consisting of 40 parts of acrylic acid, 20 parts of butyl acrylate and 40 parts of acrylonitrile, and 20 parts of water are added, and the stirring is increased to 250 rpm, and the mixture is fully mixed. The temperature is raised to 73° C., and 10 parts of an aqueous solution containing 0.6 parts of ammonium persulfate are added dropwise within 30 minutes. The mixture is kept warm for reaction for 180 minutes. After the insulation is completed, sodium bicarbonate and water are added, and the pH value is adjusted to 7.0-7.5, and the solid content is 16 wt %, to obtain a first aqueous solution.
[0052] Preparation Example 4
[0053] 400 parts of water are added to a reaction container, and a first monomer combination consisting of 40 parts of methacrylic acid, 10 parts of acrylamide, 25 parts of hydroxyethyl acrylate and 25 parts of acrylonitrile, and 5 parts of sodium bicarbonate are added under stirring at 180 rpm, and the mixture is evenly mixed. The temperature is raised to 75° C., and 10 parts of an aqueous solution containing 0.2 parts of ammonium persulfate are added dropwise within 30 minutes. After the addition is completed, the mixture is kept warm for reaction for 120 minutes, and the monomer conversion rate is measured to be 84%. A second monomer combination consisting of 15 parts of acrylic acid and 5 parts of acrylonitrile and 10 parts of water are added, and the stirring is increased to 250 rpm, and the mixture is fully mixed. The temperature is raised to 73° C., and 10 parts of an aqueous solution containing 0.2 parts of ammonium persulfate are added dropwise within 30 minutes. The mixture is kept warm for reaction for 180 minutes. After the insulation is completed, sodium bicarbonate and water are added, and the pH value is adjusted to 7.0-7.5, and the solid content is 16 wt %, to obtain a first aqueous solution.
[0054] Preparation Example 5-8 Preparation of the Second Acrylate Polymer
[0055] Preparation Example 5
[0056] Add 350 parts of water to the reaction container, continue to add 60 parts of mixed monomers (the mixed monomers consist of acrylic acid, butyl acrylate and acrylonitrile in a molar ratio of 1:1:1) and 2 parts of sodium bicarbonate, raise the temperature to 72°C, add 10 parts of an aqueous solution containing 0.3 parts of ammonium persulfate dropwise within 20 minutes, continue the reaction for 210 minutes after the addition, cool down, add a certain amount of sodium bicarbonate and water, adjust the pH to 7.0-7.5, and the solid content to 8wt%, to obtain a second aqueous solution.
[0057] Preparation Example 6
[0058] The difference between Preparation Example 6 and Preparation Example 5 is that in Preparation Example 5, the mixed monomer is replaced with equal weight parts of acrylic acid, N,N-dimethylacrylamide, butyl acrylate and acrylonitrile in a molar ratio of 1:0.5:0.5:1. The other steps remain unchanged.
[0059] Preparation Example 7
[0060] The difference between Preparation Example 7 and Preparation Example 5 is that in Preparation Example 5, the mixed monomer is replaced by equal weight parts of acrylic acid, butyl acrylate, isooctyl acrylate and acrylonitrile in a molar ratio of 2:0.5:0.5:2. The other steps remain unchanged.
[0061] Preparation Example 8
[0062] The difference between Preparation Example 8 and Preparation Example 5 is that in Preparation Example 5, the mixed monomer is replaced by equal weight parts of acrylic acid and acrylonitrile in a molar ratio of 2:1. The remaining steps remain unchanged.
[0063] Example 1
[0064] The first aqueous solution of Preparation Example 1 and the second aqueous solution of Preparation Example 5 were mixed at a weight ratio of 3:1 to obtain an aqueous adhesive.
[0065] Example 2
[0066] The first aqueous solution of Preparation Example 1 and the second aqueous solution of Preparation Example 5 were mixed at a weight ratio of 1:1 to obtain an aqueous adhesive.
[0067] Example 3
[0068] The first aqueous solution of Preparation Example 1 and the second aqueous solution of Preparation Example 5 were mixed at a weight ratio of 1:10 to obtain an aqueous adhesive.
[0069] Example 4
[0070] The first aqueous solution of Preparation Example 1 and the second aqueous solution of Preparation Example 6 were mixed at a weight ratio of 2:1 to obtain an aqueous adhesive.
[0071] Example 5
[0072] The first aqueous solution of Preparation Example 2 and the second aqueous solution of Preparation Example 6 were mixed at a weight ratio of 2:1 to obtain an aqueous adhesive.
[0073] Example 6
[0074] The first aqueous solution of Preparation Example 3 and the second aqueous solution of Preparation Example 6 were mixed at a weight ratio of 2:1 to obtain an aqueous adhesive.
[0075] Example 7
[0076] The first aqueous solution of Preparation Example 3 and the second aqueous solution of Preparation Example 7 were mixed at a weight ratio of 1:4 to obtain an aqueous adhesive.
[0077] Example 8
[0078] The first aqueous solution of Preparation Example 3 and the second aqueous solution of Preparation Example 8 were mixed at a weight ratio of 1:4 to obtain an aqueous adhesive.
[0079] Example 9
[0080] The first aqueous solution of Preparation Example 4 and the second aqueous solution of Preparation Example 7 were mixed at a weight ratio of 1:2 to obtain an aqueous adhesive.
[0081] Comparative Example 1
[0082] The first aqueous solution of Example 1 was prepared.
[0083] Comparative Example 2
[0084] The second aqueous solution of Example 2 was prepared.
[0085] Performance test comparison
[0086] The preparation process of graphite negative electrode sheet is as follows: disperse the water-based adhesive to be tested and 50% of water at 1000rpm for 15 minutes, then add the conductive agent SP conductive carbon black to wet for 12 minutes, and then stir at 1600rpm for 120 minutes; then add the negative electrode material S360-L2-H and the remaining 50% of water and continue to stir at 1600rpm for 120 minutes. After dispersion, adjust the viscosity (23℃) between 2500-2700mPa·s, and filter with a 150-mesh filter to complete the discharge. Place the copper foil on the coating machine, adjust the scraper scale of the wet film preparation device, evenly pour the filtered slurry, send it into a 100℃ environment and bake it until dry, cut it into specifications of 12.5cm×5cm, and the single-sided surface density is 100-110g / m 2 The pole piece.
[0087] The electrode peeling force test method is as follows: Place the cut electrode into a 35% RH constant temperature room for 30 minutes, with the coating facing outward and the copper foil facing inward. Lay the two electrode sheets together and place them into an electric roller press to press the electrode sheets to 1.6g / cm 3 , and then place it for 30 minutes after rolling. During this period, select five 12.5×5cm stainless steel plates, stick double-sided tape of corresponding specifications on the steel plates, and then stick the electrode on the double-sided tape with the coating facing down, and then stick a 2.5cm wide masking tape on the copper foil. The electrode steel plate is rolled back and forth by an electric rolling roller with a certain pressure for one week, and then an electronic stripper is used to test the adhesion of the electrode; the same method as above, only the electrode is stuck on the double-sided tape with the coating facing up to test the cohesion of the electrode.
[0088] The particle fineness test method of the slurry is as follows: select a suitable and clean fineness plate (range 0-50μm), use a small medicine spoon to dip the slurry and drop it on the uppermost test slot, and use a scraper to scrape it vertically and uniformly to the bottom; the scale value corresponding to the blank space that first appears on the fineness plate is the fineness value.
[0089] The assembly sequence of the button battery is from bottom to top: negative electrode shell-spring-gasket-lithium sheet-electrolyte-diaphragm-electrolyte-electrode sheet-positive electrode shell; the first coulomb efficiency and impedance test are as follows:
[0090] The first test was 0.1C, 0.005-1.5V charging and discharging; the impedance scan was from 100kHz to 0.1Hz.
[0091] The results are shown in Table 1 below.
[0092] Table 1 Performance test results
[0093]
[0094] It can be seen from the data results in Table 1 that the aqueous binder of the present application is used for dispersing the active particles of the negative electrode material, has high dispersibility, low fineness, and high cohesive strength.
[0095] The dispersion stability of the slurry obtained by the preparation of the above-mentioned graphite negative electrode sheet was tested: 90g of the freshly prepared slurry was placed in a 100ml transparent PET bottle (specifications: main body diameter 46mm, caliber 28mm, height 94mm, wall thickness 1mm), and the upper slurry was taken to test the solid content, recorded as H0; after the slurry was allowed to stand for 48 hours, the upper slurry was taken to test the solid content, recorded as H1, and the solid content change △H=H0-H1. Five samples were taken for each test, and the average value was calculated. The results are shown in Table 2 below. The smaller the change in solid content, the more stable the prepared slurry is and the better the dispersibility is.
[0096] Table 2 Dispersion stability
[0097] Slurry samples Solid content change △H / % Slurry samples Solid content change △H / % Example 1 0.27 Example 7 0.37 Example 2 0.32 Example 8 0.34 Example 3 0.29 Example 9 0.35 Example 4 0.35 Comparative Example 1 0.28 Example 5 0.31 Comparative Example 2 1.31 Example 6 0.3
[0098] It can be seen from the data results in Table 2 that the aqueous binder of the present application is used to prepare the negative electrode material active particle slurry, and the dispersion stability is good, which basically reaches the level of Comparative Example 1.
[0099] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. An aqueous binder for a negative electrode material of a lithium ion battery, characterized in that: comprising a first acrylate polymer and a second acrylate polymer; The preparation method of the first acrylate polymer is as follows: a first monomer combination consisting of a first hydrophilic monomer and a first hydrophobic monomer is polymerized in water for a first time, and then a second monomer combination consisting of a second hydrophilic monomer and a second hydrophobic monomer is added to perform a second polymerization, thereby obtaining the first acrylate polymer; The general formula of the second acrylate polymer is as shown in the following formula (1): Among them, R 1 , R 2 and R 3 independently selected from H or C1-C4 alkyl, R 4 Selected from H, Na + , Li + and K + At least one of R 5 is selected from C2-C18 alkyl, C2-C18 substituted alkyl, amino or substituted amino, R 6 The general formula is -R 7 CN, R 7 is absent or is at least one selected from C1-C4 alkylene, a>0, b≥0, c>0, a:b:c=2-5:0-4:2-5; The first hydrophilic monomer and the second hydrophilic monomer are independently selected from the general formula CH2=CR 8 R 9 The monomers, R 8 is selected from H or C1-C4 alkyl, R 9 Selected from -CONH2, -CONHCH3, -CONHCH2CH3, -CON(CH3)2, -CON(CH2CH3)2, -CONHCH2OH, -CONHCH2CH2OH, -COOCH2CH2OH, -COOCH2CH2CH2OH, -COOCH2CHCH3OH, -COOCH2CH2CH2CH2OH, -COO(CH2CH2O) a H and -COO(CH2) b PO3H, and / or one or more of the organic structures containing -COOM, -(C6H5)COOM, -SO3M and -(C6H5)SO3M functional groups, a=1-18, b=1-12, M is selected from H, Li + 、Na + and K + One or more of the following; The first hydrophobic monomer and the second hydrophobic monomer are independently selected from the group consisting of monomers having the general chemical formula CH2=CR 10 R 11 The monomers, R 10 is selected from H or C1-C4 alkyl, R 11 Selected from -COOC n H 2n+1 and -C m H 2m One or more of CN, n=1-18, m=0-6.
2. The aqueous binder for lithium ion battery negative electrode material according to claim 1, characterized in that: The concentration of the aqueous binder is 3-60 wt %.
3. The aqueous binder for lithium ion battery negative electrode material according to claim 1, characterized in that: The weight proportion of the first hydrophilic monomer in the first monomer combination is 60-100%.
4. The aqueous binder for lithium ion battery negative electrode material according to claim 1, characterized in that: The weight proportion of the second hydrophilic monomer in the second monomer combination is 0-60%.
5. The aqueous binder for lithium ion battery negative electrode material according to claim 1, characterized in that: The weight ratio of the first monomer combination to the second monomer combination is 1:9-9:
1.
6. The aqueous binder for lithium ion battery negative electrode material according to claim 1, characterized in that: After the first polymerization, the conversion rate of the first monomer combination is not less than 70%.
7. The aqueous binder for lithium ion battery negative electrode material according to claim 1, characterized in that: The weight ratio of the first acrylate polymer to the second acrylate polymer is 1:9-9:
1.
8. The method for preparing the aqueous binder for negative electrode materials of lithium ion batteries according to any one of claims 1 to 7, characterized in that: The first aqueous solution containing the first acrylic ester polymer and the second aqueous solution containing the second acrylic ester polymer are mixed.
Citation Information
Patent Citations
Battery binder, lithium ion battery negative electrode plate, and lithium ion battery
CN111500228A
Lithium ion battery negative electrode material binder
CN116314805A